Adolescents' Perceptions of "Cheating" in Gaming and Educational Settings. (April 2018) - Nease, Brandon; Samura, Michelle
Background. Given the widespread popularity ofvideo gameplay amongadolescents, it is important to understand the relationship between video gameplay and adolescent behaviors in various contexts. Aim. This exploratory study aimed to explore adolescent gamers use of player guides andcheat codes duringvideo gameplay in order to understand how they reason about the relationship betweencheating in video games and cheating inacademic settings . Method. Semi-structured interviews were conducted with adolescents in order to gain in-depth insight into participants' perspectives on video gameplay and their perceptions ofcheating in video games and academic settings. Interview data was coded and qualitatively analyzed to identify patterns and key emergent themes. Results. Findings from this exploratory study highlight seemingly contradictory views oncheating among adolescents. On the one hand, participants viewed player guides, cheat codes, and other forms of gameplay resources as simply part of the overall gaming experience. They did not view this type of assistance ascheating . On the other hand, participants viewed unsanctioned assistance and taking others' ideas as their own ascheating within academic settings . Conclusion. As findings from this study suggest, understanding how student navigatevideo gameplay may provide much needed insight into providing effective supports and tools in academic contexts. Findings from this research can inform the development of more effective approaches to addresscheating in academic settings, including the integration of study guides, student-created aids and guides and additional materials as part of an effective support system.